Safeguarding Young People Beyond the Family Home Responding to Extra- Familial Risks and Harms - Firmin, Carlene (Bristol University Press, 2022)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. During adolescence, young people are exposed to a range of risks beyond their family homes including sexual and criminal exploitation, peer-on-peer abuse and gang-related violence. However, it has only been over the past two decades that the critical safeguarding implications of these harms have started to be recognised. Social care organisations are increasingly experimenting with new approaches but continue to experience challenges in supporting affected young people and their families. This book analyses the results of the first rapid evidence assessment of social care organisations' responses to risks and harms outside the home across 10 countries. The authors highlight key areas for service development, give insights into how these risks and harms can be understood, and consider wider implications for policy and practice.